Correlational Analysis Between Compression and Tensile Mechanical Test Results of Compressed Earth Bricks CEB, Developed in the Central Andes of Peru - Gamarra Alarcon, Irvin Franco (2024)
The constant challenge of increasing quality in the manufacture of green building components and the lack of standards for the prediction of tensile strength is becoming a relevant challenge. For this reason, this research is focused on the development of a logarithmic function that relates the compressive and tensile strength of compressed earth bricks (CEB). To this purpose, the study examines the influence of different cement dosages (7%, 15% and 20%), drying days (7, 14, 21 and 28 days) and establishes critical correlations between tensile and compressive strengths. Key results indicate a proportional relationship between strength and cement dosage, with an optimal balance identified for maximum performance. A comparison was made between the proposed dosages, where the optimum was 20% cement at 28 days. In addition, a "significant positive" correlation coefficient of 0.77 is observed between the compressive and tensile strengths, which supports the proposal of a polynomial and logarithmic function for the estimation of tensile strength with a coefficient of determination (R2 ) of 87.62%. This function offers a high predictive capacity. This research provides valuable insight, laying the groundwork for future studies in assay standardization.